Effect of High-Pressure Homogenization on the Properties and Structure of Cold-Induced Chiba Tofu Gel in Soy Protein Isolate - Li Zheng; Joe M. Regenstein; Zhongjiang Wang (Gels, 2024)
In the actual production process of soy protein isolate (SPI), most of the homogeneous operating pressure is controlled below 20 MPa due to the consideration of production safety and the limitation of the pressure control capability of homogeneous equipment. In order to improve the functional properties of SPI and adapt it to actual production, the effects of different homogeneous pressures (4, 8, 10, 12, and 14 MPa) on the structure and gel properties of SPI were studied from the perspective of production control. Compared to the control group, the modified SPI improved the hardness, springiness, cohesiveness, chewiness, and water holding capacity (WHC) of the protein gel (p < 0.05). Rheological analysis shows that both G′ and G″ increase with increasing frequency, reaching a maximum at 12 MPa. The gel intermolecular force results show that the disulfide bond, hydrophobic interaction, and non-disulfide bond are important molecular forces for gel formation. The particle size distribution uniformity of modified SPI was high, and scanning electron microscopy (SEM) analysis showed that the protein gel with a continuous uniform and dense network structure could be formed by high-pressure homogeneous modification. Overall, high-pressure homogenization technology has the potential to improve SPI gel structure and WHC, and 12 MPa modified SPI gel has the most significant effect.